2021
DOI: 10.3400/avd.cr.21-00011
|View full text |Cite
|
Sign up to set email alerts
|

Successful Combined Treatment of Giant Carotid Body Tumor with Embolization Applied before Surgery

Abstract: Carotid body tumors are defined as unusual tumors of neuroectodermal origin that occur in the carotid bifurcation. These generally benign masses grow slowly; then, they become symptomatic with enlargement. In this study, we present a case of a 66-year-old female patient diagnosed with a carotid body tumor with a diameter of 8×9×10 cm. The patient was surgically treated 2 days after embolization due to the wideness of the mass and surgical comorbidity. Furthermore, this article puts emphasis on the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…There are few reports on MRI in the diagnosis of CBTs. MRI delineates the extent of a tumor, its vascularity, the condition of the carotid vessels, and the presence of other swellings or enlarged nodes and is a good alternative to CT [ 7 ].…”
Section: Case Historymentioning
confidence: 99%
“…There are few reports on MRI in the diagnosis of CBTs. MRI delineates the extent of a tumor, its vascularity, the condition of the carotid vessels, and the presence of other swellings or enlarged nodes and is a good alternative to CT [ 7 ].…”
Section: Case Historymentioning
confidence: 99%
“…Carotid body tumors (CBT) are highly vascular, glomus tumors arising from paraganglion cells of the carotid body. They represent only 0.6% of head and neck tumors and are usually benign with a metastasis rate of 2%–9% 1,2 . While they are usually benign, the location and growth of these tumors can lead to symptoms of enlarging neck mass, dysphagia, voice changes, headache, syncope, Horner syndrome, and compressive symptoms of cranial nerves IX, X, XII and the sympathetic chain 1 .…”
Section: Introductionmentioning
confidence: 99%
“…They represent only 0.6% of head and neck tumors and are usually benign with a metastasis rate of 2%–9% 1,2 . While they are usually benign, the location and growth of these tumors can lead to symptoms of enlarging neck mass, dysphagia, voice changes, headache, syncope, Horner syndrome, and compressive symptoms of cranial nerves IX, X, XII and the sympathetic chain 1 . Most CBT's are nonfunctional, but catecholamine‐producing tumors are possible leading to symptoms of paroxysmal hypertension 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative transarterial embolization (pre-TAE) decreased the overall blood loss (BL) and improved visualization at surgery, thus facilitating tumor resection, which was first introduced by Schick et al in 1980 (9). Since then, several studies have evaluated the impact of pre-TAE on CBT surgery (4,(10)(11)(12)(13)(14)(15)(16)(17). The results demonstrated that pre-TAE is an effective and safe adjunct for surgical resection that can reduce BL and operative time during surgery and decrease the risk of perioperative complications, especially for Shamblin class II/III tumors.…”
Section: Introductionmentioning
confidence: 99%